The level of depression, anxiety, stress and coping strategies in parents with congenital talipes equinovarus children - Awang, Mohd Shukrimi; Abdul Razak, Ardilla Hanim; Azizi, Nurazlina; Bukhori, Nur Amalina Syazwani; Mohamad Zainuddin, Hanisah; Mat Zin, Nora (Kulliyyah of Medicine, International Islamic University Malaysia, 2017)
Introduction: Having children with congenital anomalies, particularly congenital talipes equinovarus (CTEV) may impact the psychological wellbeing of the parents. This study is to assess the psychological impact of CTEV, the related factors, and the coping strategies used by the parents in Hospital Tengku Ampuan Afzan (HTAA), Kuantan, Pahang.